Теплообмен за двойным рядом поверхностных генераторов цилиндрической и сферической формы - Халатов, А.А.; Онищенко, В.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The experimental data on the heat transfer on a flat plate after the double array of surface indentations are given. The transition to the turbulent flow after the indentations occurs according to the “bypass” mechanism. It is shown that the shape, depth, and span-wise pitch do not influence the heat transfer intensity after the double array of indentations.